Why Current Detection of Vascular Calcification Falls Short and How to Improve on It - Gentier, Anouk; Aizaz, Mueez; Halder, Maurice; Florea, Alexandru; Dijkgraaf, Ingrid; Mottaghy, Felix M.; Hackeng, Tilman; Kooi, M Eline (TH Open, 2024)
Vascular calcification is a common phenomenon in various vascular diseases, where its presence heralds increased occurrence of adverse disease events, which invariably lead to increased morbidity and mortality in patients. Although the impact of calcification has become apparent, adequate and early detection of the most damaging form of early microcalcification is still in its infancy, preventing reliable identification of locations that would benefit from intervention. In this review, we will provide an overview of the current state-of-the-art noninvasive calcification imaging and its persisting limitations. We discuss promising approaches that may address these limitations in the future. In this context particular attention will be paid to imaging modalities such as CT, PET, and ultrasonography and molecular and cellular mechanisms and agents involved in physiological bone formation.
Keywords: imaging; cardiovascular disease; noninvasive imaging; early detection; vascular calcification